Computer Science & Technology Series : XVII Argentine Congress of Computer Science. Selected papers - De Giusti, Armando Eduardo (2012)
CACIC’11 was the seventeenth Congress in the CACIC series. It was organized by the School of Computer Science of the University of La Plata. The Congress included 11 Workshops with 148 accepted papers, 3 main Conference, 4 invited tutorials, different meetings related with Computer Science Education (Professors, PhD students, Curricula) and an International School with 5 courses. (http://www.cacic2011.edu.ar/). CACIC 2011 was organized following the traditional Congress format, with 11 Workshops covering a diversity of dimensions of Computer Science Research. Each topic was supervised by a committee of three chairs of different Universities. The call for papers attracted a total of 281 submissions. An average of 2.5 review reports were collected for each paper, for a grand total of 702 review reports that involved about 400 different reviewers. A total of 148 full papers, involving 393 authors and 77 Universities, were accepted and 25 of them were selected for this book.